Effect of Kappaphycus alvarezii and Overripe Banana Sweetener Addition on the Nutritional Composition and Palatability of Cookies - Nie, Linlin; Wan Ishak, Wan Rosli; Mohd Kamil, Khadijah; Majahar Ali, Majid Khan (Jurnal Gizi dan Pangan, 2024)
This study aimed to assess the qualities of butter biscuits made with seaweed flour (Kappaphycus alvarezii, (KA) (0, 4, and 8%) and Overripe Banana Sweetener (ORBS) (0, 50, and 100%) as a partial replacement for wheat flour and table sugar. A.O.A.C. and hedonic methodologies have been used to analyze the nutritional composition, color, and sensory evaluation of butter cookies. The increase in ORBS in cookie formulation resulted in a significant rise in the nutritional qualities of butter cookies, according to the result. Butter cookies with 4% seaweed flour and 100% ORBS had higher total dietary fiber (19.6%) and ash (3.07%) values. Sensory scores for the control (0%) and 4% seaweed flour-incorporated cookies did not differ substantially across all sensory qualities. However, the addition of 4% seaweed flour and 50% ORBS resulted in the highest scores for aroma, flavor, and overall acceptance. In conclusion, substituting 4% seaweed flour for wheat flour and 50% ORBS for table sugar could be an effective combination to make nutritious and tasty butter cookies.